2022
DOI: 10.3847/1538-4357/ac59b0
|View full text |Cite
|
Sign up to set email alerts
|

Chromospheric Carbon Monoxide Formation around a Solar Pore

Abstract: We present observations of NOAA AR 11159, obtained on 2011 February 14 in the 4.7 μm band of carbon monoxide (CO) and coordinated with spectroscopic imaging of three atomic lines (Na i 5896 Å, Fe i 7090 Å, and Ca ii 8542 Å) which sample heights from the mid-photosphere to the chromosphere. Phase-difference spectra between the observed spectral lines instead indicate that the CO lines form at z ≈ 530−650 km in the quiet Sun. During the two hours of observations, seven long-lived cooling events (“cold bubbles”) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 37 publications
2
5
0
Order By: Relevance
“…The very existence of a strong horizontal magnetic field in a region of cold bubbles (Fig. 3 (b) and (c)) supports the explanations of both Ayres (1981) and Stauffer et al (2022).…”
Section: Conclusion and Discussionsupporting
confidence: 75%
See 4 more Smart Citations
“…The very existence of a strong horizontal magnetic field in a region of cold bubbles (Fig. 3 (b) and (c)) supports the explanations of both Ayres (1981) and Stauffer et al (2022).…”
Section: Conclusion and Discussionsupporting
confidence: 75%
“…This result suggests "cold bubbles" exist with different magnetic field structures, including unipolar, bipolar, or even more complicated structures. In recent work, Stauffer et al (2022) also reported the CO "cold bubbles" observed in the region surrounding a large pore, indicating a potential role of the magnetic field in the formation of these "cold bubbles".…”
Section: Results From Cyra Observationmentioning
confidence: 89%
See 3 more Smart Citations